Typologia rodzin wielkoarmejskich środowisk według kryteriów wydolności wychowawczej i stymulacji kulturalnej - Sosnowski, Adam; Walkowiak, Jerzy (Wydział Prawa i Administracji UAM, 1986)
The article is presenting a fraction of survey results obtained during the iresearch of housing estate circles of Szczecin and Poznań. It concerns family circles of housing estate neighbourhood youth in the age of 13 - 20, studying and not working. The authors start with the sociological understanding of a family and its basic functions. In further part of the study they (present and discuss categories of youth differentiated by them. Criteria of differentiation were the following: 1) level of social adaptation, 2) level of social, cultural and educational activeness. The "exemplary" youth is the first of the mentioned categories. Its functioning in the family is characterized by the incentive to cooperate with the remaining members of that genetical group and appearing conflicts have a creative and developing character. That part of youth consists of almost one fifth of the whole population. The next category described as "average" youth differs from the rest by means of the emotional ties with their families of origin and by drawing from it patterns for the created models and visions of their family of procreation, especially in social and educational spheres. That part of the examined equals one half of the neighbourhood youth. The final category, subdivided into the "difficult" youth from the social marigin and the youth in conflict with law is characterized by loose ties with a family and little relations with a wider social environment. Representatives of that category consist over the third part of the whole category of youth.
Typology of Families in Urban Environment According to the Criteria of Educational and Cultural Influence